Amide Bond Formation Catalyzed by Recyclable Copper Nanoparticles Supported on Zeolite Y under Mild Conditions. Issue 5 (7th February 2019) - Moglie, Yanina; Buxaderas, Eduardo; Mancini, Agustina; Alonso, Francisco; Radivoy, Gabriel
Abstract: A series of catalysts based on supported copper nanoparticles have been prepared and tested in the amide bond formation from tertiary amines and acid anhydrides, in the presence of tert ‐butyl hydroperoxide as an oxidant. Copper nanoparticles on zeolite Y (CuNPs/ZY) was found to be the most efficient catalyst for the synthesis of amides, working in acetonitrile as solvent, under ligand‐ and base‐free conditions in air. The products were obtained in good to excellent yields and in short reaction times. The CuNPs/ZY system also exhibited higher catalytic activity than some commercially available copper and iron sources and it was reused in ten reaction cycles without any further pre‐treatment. This methodology has been successfully scaled‐up to a gram scale with no detriment to the yield. Abstract : Better Call Copper : If you need tertiary amides, this is a case for copper! Recyclable copper nanoparticles (CuNPs) supported on Zeolite Y allow access to a variety of tertiary amides in a simple and economic way, even in gram scale.